Does prevention as an investment strategy explain the intention to purchase guarantees for unit-linked life insurance?. Issue 3 (December 2018) - Luca, Daliana
Abstract The present paper examines the relationship between prevention as an investment strategy and the perceptions about unit-linked insurance on the intention to purchase interest rate guarantees for such products. We propose a framework in which the relationship between adopting prevention as an investment strategy, and the intention to purchase interest rate guarantees is moderated by the level of financial literacy of the individual and this interaction is mediated by the perceptions regarding unit-linked insurance. We find support for our conceptual model by testing it on a sample of 1017 financial decision makers in Germany using a moderated mediation analysis. The paper therefore offers insights into the decision-making process of financial consumers in Germany and presents practical implications for designing products for age-old provision.